2015
DOI: 10.1111/iju.12836
|View full text |Cite
|
Sign up to set email alerts
|

Establishment and value assessment of efficacy prediction model about transurethral prostatectomy

Abstract: Abbreviations & Acronyms AUC = area under the curve AUR = acute urinary retention BCI = bladder contractility index BOO = bladder outlet obstruction BOOI = bladder outlet obstruction index BWT = bladder wall thickness DO = detrusor overactivity DWT = detrusor wall thickness IPP = intravesical prostatic protrusion IPSS = International Prostate Symptom Score IPSS -s = storage score IPSS -v = voiding score LUTS/BPO = lower urinary tract symptoms suggestive of benign prostatic obstruction MODS = multiple organ dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
6
1
Order By: Relevance
“…However acceptable tools for noninvasively distinguishing BOO from DU have yet to be identified 8 , 28 . Huang et al 29 analyzed that increased BWT was associated with ineffective recovery of IPSS, QoL score and Qmax after surgery (OR 0.78, 95% CI 0.72–0.84). The DMT was analyzed as an independent predictor of surgical efficacy of IPSS, QoL score and Qmax (OR 2.05, p = 0.036; AUC 0.762, cutoff value 15 mm at the bladder volume of 250 mL) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…However acceptable tools for noninvasively distinguishing BOO from DU have yet to be identified 8 , 28 . Huang et al 29 analyzed that increased BWT was associated with ineffective recovery of IPSS, QoL score and Qmax after surgery (OR 0.78, 95% CI 0.72–0.84). The DMT was analyzed as an independent predictor of surgical efficacy of IPSS, QoL score and Qmax (OR 2.05, p = 0.036; AUC 0.762, cutoff value 15 mm at the bladder volume of 250 mL) 30 .…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Seki et al, multiple logistic regression analysis indicated that a higher baseline level of BOOI was associated with greater improvements in IPSS and QoL. Huang et al conducted a study to establish an e cacy prediction model for transurethral prostatectomy, and found that there was a positive correlation between surgical e cacy with a higher degree of BOO and secondary detrusor cell hypertrophy [17]. Similarly, previous studies have shown that patients with de nite BOO derive greater bene t from TURP surgery than those with equivocal and unobstruction [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…In a study by Seki et al, multiple logistic regression analysis indicated that a higher baseline level of BOOI was associated with greater improvements in IPSS and QoL. Huang et al conducted a study to establish an efficacy prediction model for transurethral prostatectomy, and found that there was a positive correlation between surgical efficacy with a higher degree of BOO and secondary detrusor cell hypertrophy [ 19 ]. Similarly, previous studies have shown that patients with definite BOO derive greater benefit from TURP surgery than those with equivocal and unobstruction [ 20 , 21 ].…”
Section: Discussionmentioning
confidence: 99%